2019
DOI: 10.5653/cerm.2019.46.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression analysis of human cumulus cells

Abstract: Objective This study was performed to explore the possibility that each oocyte and its surrounding cumulus cells might have different genetic expression patterns that could affect human reproduction. Methods Differential gene expression analysis was performed for 10 clusters of cumulus cells obtained from 10 cumulus-oocyte complexes from 10 patients. Same procedures related to oocyte maturation, microinjection, and microarray analyses were performed for each group of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 50 publications
(54 reference statements)
1
5
0
1
Order By: Relevance
“…The findings of the present research suggested that the W. somnifera has protective effect against morphine on the regulation of hormone as proved in Tables 1 and 2 which illustrated that promotive and protective effect of W. somnifera against noxious effect of the morphine, the result approved and assert by the previous studies, which Karimi et al, 2018 [26] showed that administration of morphine leads to irregulating and disturbance on the hypothalamus pituitary ovary axis and causes anovulatory infertility [32]. Scientists suggested that mechanism effect of morphine is related to the nature of the opioid receptors pharmacokinetic [26]; which morphine has inflammatory effects on the ovary due to causes increase in the secretion of LH in response to GnRH [33], and by inhibit effect of insulin in liver which that stimulate the pancreas for production of insulin [34], then, causes hyperinsulinemia in the polycystic ovary.…”
Section: Discussionsupporting
confidence: 74%
“…The findings of the present research suggested that the W. somnifera has protective effect against morphine on the regulation of hormone as proved in Tables 1 and 2 which illustrated that promotive and protective effect of W. somnifera against noxious effect of the morphine, the result approved and assert by the previous studies, which Karimi et al, 2018 [26] showed that administration of morphine leads to irregulating and disturbance on the hypothalamus pituitary ovary axis and causes anovulatory infertility [32]. Scientists suggested that mechanism effect of morphine is related to the nature of the opioid receptors pharmacokinetic [26]; which morphine has inflammatory effects on the ovary due to causes increase in the secretion of LH in response to GnRH [33], and by inhibit effect of insulin in liver which that stimulate the pancreas for production of insulin [34], then, causes hyperinsulinemia in the polycystic ovary.…”
Section: Discussionsupporting
confidence: 74%
“…CCs are the somatic cells surrounding the oocyte. They play an important role in the growth of the oocyte, meiotic maturation, ovulation, and fertilization in mammalians [ 4 ]. CCs originate from undifferentiated granulosa cells (GCs) from primordial to preantral follicles.…”
Section: The Definition Of Cumulus Cells and The Differentiation Of Granulosa Cellsmentioning
confidence: 99%
“…Differential gene expression analysis of the 10 clusters of cumulus cells obtained from 10 cumulus–oocyte complexes from 10 patients was performed. Circadian entrainment is the most affected pathway in clinical pregnancy [ 35 ], which indirectly indicates that circadian entrainment affects the reproductive cycle. According to previous studies, the Rap-1 signaling pathway has an impact on reproduction [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%